Wave - Lee, Suzy. (San Francisco : Chronicle Books, 2008)
A wordless book in which a young girl experiences the power of ocean waves.
Kirkus Starred
Pub Weekly
School Library Journal starred
K-3
K-3
Keywords: Waves -- Juvenile fiction; Stories without words; Waves -- Fiction; Stories without words; Waves -- Fiction